Preliminary study on Semedo’s bone artifacts, Tegal, Central Java: Kajian awal artefak tulang Situs Semedo di Tegal, Jawa Tengah - Arjanto, Dama Q.; Dewi, Intan Kemala (Berkala Arkeologi, 2024)
Bone artifacts as a cultural product of the hominins are rarely found in Pleistocene Sites in Indonesia. Among a few Pleistocene sites yielding bone artifacts, Semedo in Central Java provides it along with numerous fossils, including Homo erectus and stone artifacts. This is why the studies on the bone artifacts from Semedo are important. This paper tries to present the study results on three specimens of bone artifacts based on a morphological approach. The study shows that the three specimens are convincingly identified as culturally modified bone fragments. It is inferred from the fracture morphology and the grinding marks on the specimens. Some striations are also visible from the specimens, indicating the possible function of the fragments as tools. However, due to its secondary deposits and postdepositional transportation, it isn't easy to correlate chronologically with artifacts from other sites, despite technological character similarities. Nevertheless, this paper could provide more information on Pleistocene bone artifacts from the Indonesian archipelago.